Pembelajaran Tari Legong Lasem Di Sanggar Tari Warini - Cahyanthi, Ni Komang Putri; Arshiniwati, Ni Made; Ardhika, I Gusti Lanang Oka (Jurnal IGEL : Journal Of Dance, 2022)
Legong Lasem Dance Lesson at Warini Dance Studio Legong Lasem dance is danced by 3 female dancers including 1 Condong dancer and 2 Legong dancers. Legong Lasem dance tells the love did not reach Prabu Lasem to Princess Rangkesari. Legong Lasem dance prioritiez aesthetic movements, and there are also elements of expression or drama. This studi examines how the Legong Lasem dance learning method is at the Warini Studio, how the Legong Lasem dances enthusiasts are at the Warini Studio, and how are the Legong Lasem dance learning outcomes at the Warini Studio as an effort to increase students understanding of Legong Lasem dance. This study uses a qualitative approach with data collection techniques through observation, interviews, and documentation, uses 2 methods, namely demonstration and imitation. Legong Lasem dance is one of the mandatory materials taught at the Warini dance studio, because this dance is the basis of other dances. The results obtained from this study are able to know the process of learning the Legong Lasem dance in the Warini dance studio as a basis for training dance, thus giving birth to dancers who have strong qualities and techniques due to the will of dancer and the most important thing is the perseverance and patience of a dance maestro, Ms. Arini. Keywords : Legong Lasen dance, method, results